«Para que sea memoria, y que se ponga en el archibo»: Literature and History in Colonial Latin America. An Interview with Rolena Adorno - Rohner, Stephanie (2021)
In this interview, Rolena Adorno, scholar of Latin American colonial literature, offers a reflection on her research on the chronicler Guaman Poma de Ayala and other authors of the colonial period. She discusses how she became interested in the subject, the maturation of her methodology, and the legacy of her publications.